Increasing Awareness Of Business Persons In The Use Of Cloud Pos PT. Guest Pro Indoensia - Kadek Krisna Saputra; Kadek Wulandari Laksmi P; I G. N. Oka Ariwangsa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
PT. Guest Pro Technology Indonesia as the place where the author carries out street vendors is a technology company that has a vision to become an integrated technology platform to maintain and develop 246 trillion rupiah of tourism foreign exchange potential so that it can be enjoyed maximally by every tourism industry player in Indonesia. In this article, the author conveys how to increase public awareness and culinary business actors in recognizing and feeling the benefits of using the Cloud POS operating system which makes culinary business services more efficient and of course increases performance effectiveness. In this case, the use of the operating system from PT. Guest Pro Technology called Cloud POS. By using the method of observation and interviews in the implementation of activities, the authors play a role in promoting and explaining the superiority of products from PT. Guest Pro to the public in general and culinary business actors in particular.